A new species of the genus Paraxenos Saunders, 1872 (Strepsiptera: Xenidae) from Bembix digger wasps (Hymenoptera: Bembicidae) and a redescription of Paraxenos hungaricus (Székessy, 1955) - Benda, Daniel; Pohl, Hans; Nakase, Yuta; Beutel, Rolf; Straka, Jakub (European Journal of Taxonomy, 2023)
A new species of Strepsiptera of the genus Paraxenos Saunders, 1872 (Xenidae) from the United Arab Emirates is described. It was recorded from the host species Bembix kohli Morice, 1897 and represents the first occurrence of Paraxenos from Bembix Fabricius, 1775 in the Afrotropical region. A detailed redescription of the female cephalothorax of Paraxenos hungaricus (Székessy, 1955) is provided, together with the first description of the male cephalotheca. The holotype of Paraxenos krombeini Kifune & Hirashima, 1987 was redescribed. Additionally, a key for parasites of Bembix among Paraxenos species is provided based on characters of the female cephalothorax and male cephalotheca. The distribution and conservation status of Paraxenos spp. on Bembix are also discussed.